2021
DOI: 10.1080/09620214.2021.1886594
|View full text |Cite
|
Sign up to set email alerts
|

Enacting school self-evaluation: the policy actors in Irish schools

Abstract: School self-evaluation is a low-stakes policy recently mandated in Ireland and while schools are becoming more consistent in engaging in this internal mode of evaluation, their engagement has not been uniform. This paper provides new ways of thinking about, understanding, and explaining how school self-evaluation plays out in Irish schools. Subscribing to the view that policies are not simply implemented but enacted through the creative processes of interpretation and translation, this paper shows how school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…(Ball, Maguire, and Braun 2012, 10) While SSE is at present officially focused more on improvement than accountability, student voice does present, even unintentionally, opportunities for the monitoring of teacher performance. It would perhaps be naive to not consider that this is now occurring in schools, and there are signs that this is taking place (see Skerritt et al 2021). The arrival of the Student and Parent Charter Bill could possibly give rise to increased surveillance.…”
Section: Combining Theories: Consultations On Classroom Practice In Irish Post-primary Schoolsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Ball, Maguire, and Braun 2012, 10) While SSE is at present officially focused more on improvement than accountability, student voice does present, even unintentionally, opportunities for the monitoring of teacher performance. It would perhaps be naive to not consider that this is now occurring in schools, and there are signs that this is taking place (see Skerritt et al 2021). The arrival of the Student and Parent Charter Bill could possibly give rise to increased surveillance.…”
Section: Combining Theories: Consultations On Classroom Practice In Irish Post-primary Schoolsmentioning
confidence: 99%
“…(Salokangas, Wermke, and Harvey 2020, 343) It is not necessarily solely principals undertaking surveillance, however. The current authors have found that some post-holders in Irish post-primary schools engage in policy monitoring and monitor the work of teachers through student voice initiatives such as surveys (see Skerritt et al 2021).…”
Section: Are Management-level Consultations Becoming More Common?mentioning
confidence: 99%
See 2 more Smart Citations
“…In this new realm of allegedly greater school autonomy, inspection regimes have emerged in most countries, even those with no such tradition but, again somewhat paradoxically, alongside a drive for control and regulation by external inspectors, most inspection regimes give greater or lesser emphasis to some form of internal regulation, often referred to as SSE (Brown et al, 2018). School self-regulation or SSE is expected to be conducted, at least to some extent and within an externally designed structure, by the “stakeholders,” school leaders, teachers, parents, and students (Brown et al, 2019, 2020a; Brown, McNamara et al, 2021; Skerritt et al, 2021). This, supposedly, “reflects the democratic values of participation and transparency” (Kyriakides & Campbell, 2004, p.24) of schools as the judgment about the quality of education provision is made by those who are most affected (students and parents) or who affect it the most (teachers and school leaders).…”
Section: Literature Reviewmentioning
confidence: 99%